A REVIEW ON MONETARY VALUATION OF THE ENVIRONMENTAL IMPACTS OF TRAFFIC - Chiquetto, Sergio (Transportes, 1994)
Environmental resources are finite and scarce. According to the economic theory, value arises whenever satisfaction is derived to individuals. As environmental attributes represent a source of satisfaction, certain economic values are somehow associated to them. As a consequence, environmental externalities may result in costs to the economic system. Environmental valuation has become important in decision-making for appraisals of projects arid schemes, as well as in the management of natural resources. Although subject to several criticisms, many techniques have been developed to assign monetary values to environmental goods and assets. Besides, many attempts have been made on the application oil such techniques for actual money estimates. This paper presents a review on the environmental valuation of traffic-induced effects. Initially, some economic basis for environmental valuation is given, as well as a description of the main techniques, their applicability and disadvantages. A brief discussion about the economic instruments on environmental damaging activities is also presented. Further, a guidance on the valuation of some predominant adverse effects of traffic is provided. Resumo: Os recursos ambientais são finitos e escassos. De acordo com a teoria econômica, valor surge sempre que satisfação é derivada a indivíduos. Se atributos ambientais representam uma fonte de satisfação, certos valores econômicos são de alguma forma associados a eles. Como conseqüência, externalidades ambientais podem ocasionar custos ao sistema econômico. Avaliação ambiental passou a ser importante em tomada de decisão para analise de projetos e planos, bem como para o gerenciamento dos recursos naturais. Embora sujeitas a varias críticas, diversas técnicas foram desenvolvidas para alocar valores monetários a bens ambientais. Alem disto, muitas tentativas foram feitas no sentido de aplicar tais técnicas a fim de produzir, de fato, estimativas monetárias. Este trabalho apresenta uma revisão sobre avaliação ambiental dos efeitos induzidos pelo trafego. Inicialmente uma base econômica para avaliação ambiental e reportada, assim como uma descrição das principais técnicas existentes suas aplicabilidades e desvantagens. Uma breve discussão sobre os instrumentos econômicos aplicados a atividades que causam danos no meio ambiente é apresentada. Finalmente, uma orientação sobre avaliação monetária de alguns efeitos adversos predominantes do trafego é fornecida.